Salicylanilide acetates: synthesis and antibacterial evaluation - Vinsova, Jarmila; Imramovsky, Ales; Buchta, Vladimir; Ceckova, Martina; Dolezal, Martin; Staud, Frantisek; Jampilek, Josef; Kaustova, Jarmila (Molecules (Basel, Switzerland), 2007)
A new series of salicylanilide acetates was synthesized and evaluated for their in vitro antifungal and antituberculotic activity. Some of the evaluated compounds possessed comparable or better antifungal activity than a fluconazole standard. All these compounds exhibited very good potential and their in vitro activity against drug resistant and sensitive clinical isolates of Mycobacteria were found to be equivalent or better than a standard of isoniazide, a well-known first-line drug for tuberculosis treatment.
Keywords: Cell Survival; Microbial Sensitivity Tests; Humans; Fluconazole; vztahy mezi strukturou a aktivitou; antifungální látky; mikrobiální viabilita; Structure-Activity Relationship; flukonazol; mikrobiální testy citlivosti; lidé; antibakteriální látky; Microbial Viability; molekulární struktura; Molecular Structure; buněčné linie; Cell Line; Anti-Bacterial Agents; Antifungal Agents; Mycobacterium; salicylanilidy; Salicylanilides; Candida albicans; viabilita buněk